2002
DOI: 10.1046/j.1524-475x.2002.10801.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human platelet‐derived growth factor and transforming growth factor‐β mediated contraction of human dermal fibroblast populated lattices is inhibited by Rho/GTPase inhibitor but does not require phosphatidylinositol‐3′ kinase

Abstract: Matrix reorganization and tissue contraction are essential for wound healing. However, the intracellular signals that mediate these processes are largely unknown. We investigated cytokine-induced signaling and its potential role in contraction of adult human dermal fibroblast populated collagen lattices. The results document that recombinant human platelet-derived growth factor-BB and transforming growth factor-1 individually stimulate contraction of fibroblast populated collagen lattices, while a combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Exogenously added TGF-b1 accelerated DE contraction in our study in agreement with numerous previous reports [24][25][26][27][28][29][30]. TGF-b1 is thought to regulate DE contraction by altering the composition and tertiary structure of the ECM as well as integrin expression [28,41] but without influencing DNA synthesis in the fibroblasts [42].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Exogenously added TGF-b1 accelerated DE contraction in our study in agreement with numerous previous reports [24][25][26][27][28][29][30]. TGF-b1 is thought to regulate DE contraction by altering the composition and tertiary structure of the ECM as well as integrin expression [28,41] but without influencing DNA synthesis in the fibroblasts [42].…”
Section: Discussionsupporting
confidence: 91%
“…The PDGF-AA and PDGF-BB isoforms caused more rapid contraction than did TGF-b1 in a similar DE system to ours [24]. Furthermore, another group showed that the effect of PDGF-BB and TGF-b1 on DE contraction was additive [27] through independent signalling pathways [24]. This is a plausible explanation for the significantly higher response of both EMP and amelogenin than TGF-b1 treatment alone.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Consistent with these data, we observed rapid pseudopodial and/or filopodial extension coincident with cell relaxation after Rho-kinase inhibition, suggesting a relative increase in Rac activity. Others have demonstrated that Rho or Rho-kinase inhibition decreases the overall contraction of collagen matrices, 45,63,89 reduces force generation by a mass culture of cells, 90 and blocks LPA-induced retraction of dendritic cell processes in floating collagen matrices. 91 However, to our knowledge, this is the first study to demonstrate directly the effect of Rho-kinase inhibition on the subcellular pattern of force generation by individual cells in a 3-D model.…”
Section: Discussionmentioning
confidence: 99%